A STUDY ON ROLE OF DIGITAL BONDING IN RECONSTRUCTING WOMEN’S ECONOMIC EMPOWERMENT WITH RESPECT TO STREET VENDORS - Khandagale, Aniket Sanjay; Shetiya, Mahavir Manikchand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study aimed to examine the impact of online banking services on women empowerment with reference to street vendors in Pune region. The study used a mixed-method approach, which included surveys and interviews with street vendors in the region. The results indicate that online banking services have a significant impact on women empowerment, as they provide greater financial autonomy and access to credit. The study concludes by providing recommendations for policy-makers and practitioners to promote the use of online banking services among women street vendors.